Intensity-Value Corrections for Integrating Sphere Measurements of Solid Samples Measured behind Glass. Issue 11 (November 2014) - Johnson, Timothy J.; Bernacki, Bruce E.; Redding, Rebecca L.; Su, Yin-Fong; Brauer, Carolyn S.; Myers, Tanya L.; Stephan, Eric G.
Accurate and calibrated directional-hemispherical reflectance spectra of solids are important for both in situ and remote sensing. Many solids are in the form of powders or granules and to measure their diffuse reflectance spectra in the laboratory, it is often necessary to place the samples behind a transparent medium such as glass for the ultraviolet (UV), visible, or near-infrared spectral regions. Using both experimental methods and a simple optical model, we demonstrate that glass (fused quartz in our case) leads to artifacts in the reflectance values. We report our observations that the measured reflectance values, for both hemispherical and diffuse reflectance, are distorted by the additional reflections arising at the air–quartz and sample–quartz interfaces. The values are dependent on the sample reflectance and are offset in intensity in the hemispherical case, leading to measured values up to ∼6% too high for a 2% reflectance surface, ∼3.8% too high for 10% reflecting surfaces, approximately correct for 40–60% diffuse-reflecting surfaces, and ∼1.5% too low for 99% reflecting Spectralon® surfaces. For the case of diffuse-only reflectance, the measured values are uniformly too low due to the polished glass, with differences of nearly 6% for a 99% reflecting matte surface. The deviations arise from the added reflections from the quartz surfaces, as verified by both theory and experiment, and depend on sphere design. Empirical correction factors were implemented into post-processing software to redress the artifact for hemispherical and diffuse reflectance data across the 300–2300 nm range.